It's okay to manage your boss the step-by-step program for making the best of your most important relationship at work - Tulgan, Bruce (San Francisco, Calif Jossey-Bass Chichester John Wiley [distributor], 2010)
"Get what you need from your boss. In this follow-up to the bestselling It's Okay to Be the Boss, Bruce Tulgan argues that as managers demand more and more from their employees, they are also providing them with less guidance than ever before. Since the number one factor in employee success is the relationship between employees and their immediate managers, employees need to take greater responsibility for getting the most out of that relationship. Drawing on years of experience training managers and employees, Tulgan reveals the four essential things employees should get from their bosses to guarantee success at work. Shows employees how to ask for what they need to succeed in their high-pressure jobs. Shatters previously held beliefs about how employees should manage up. Outlines what employees must get from their managers: clear expectations; the skills needed to perform their jobs; honest feedback, recognition or rewards. A novel approach to managing up, It's Okay to Manage Your Boss is an invaluable resource for employees who want to work more effectively with their managers."--
Includes index
1
Keywords: Managing your boss